Quality of life of caregivers of patients with gastrointestinal cancer: relationship of sex, age, and stage of the cancer patients - Rosa, Lilian Nascimento; Forones, Nora Manoukian (Brazilian Journal of Oncology, 2022)
Introduction: The caregivers of cancer patients may experience changes in their routine that affect their quality of life. The aim of the study was to identify the domains that compromise the quality of life (QoL) of the caregivers of patients with gastrointestinal cancer (GIC).Methods: A descriptive, observational study with caregivers of patients diagnosed with GIC during chemotherapy therapy was done. The caregivers answered 2 questionnaires, SF-36 (short form health survey 36) and CBS (caregiver burden scale).Results: 100 caregivers of 100 patients with GIC were included. The mean age of the patients was 62.2±13 years. Most of them had colorectal cancer (66%), ECOG 0-1 (87%) and stage II/III (81%) disease. Among caregivers, 81% had less than 60 years old and 76% were female. According to the SF-36, lower levels were observed in the emotional, physical aspects and vitality and the best average in functional capacity. Regarding the CBS instrument, the general strain domain and disappointment was the more affected. Stage or ECOG was not associated to the caregivers QOL or burden. High schooling level of the patients was associated with a better quality of life and less burden of the caregivers. Ageing caregivers had a worst QoL and an increased burden.Conclusion: Most of caregivers were women and youngers, and had a worst quality of life in emotional role, physical aspects and vitality, and an increased burden in general strain and disappointment.
Keywords: Caregivers; Quality of life; Gastrointestinal cancer